Second allogeneic stem cell transplantation in acute leukemia patients: single-centre experience - Uncu Ulu, Bahar; Dal, Mehmet Sinan; Bakırtaş, Mehmet; Yiğenoğlu, Tuğçe Nur; Başcı, Semih; Özcan, Nurgül; İskender, Dicle; Kızıl Çakar, Merih; Altuntaş, Fevzi (Jurnal Teknologi Laboratorium, 2020)
Acute leukaemia patients who relapse after the first allogeneic stem cell transplantation (Allo-SCT) have a poor prognosis. Participating in clinical trials is the best option for these patients. If patients cannot participate in clinical trials, as the treatment options are limited, the second allo-SCT constitutes the potential curative treatment option. The data of acute leukaemia patients who underwent second allo-SCT because of relapsed/refractory disease after the first allo-SCT at our centre between December 2009 and February 2019 were analyzed retrospectively. Three hundred nineteen acute leukaemia patients were performed allo-SCT at our centre. 20 of these 319 acute leukaemia patients relapsed after first allo-SCT and underwent second allo-SCT. 10 AML patients and 10 ALL patients were included in the study. After second allo-SCT overall survival (OS) was 26.1±10.8 weeks, and progression-free survival (PFS) was 19.9±8.6 weeks. If the patients cannot participate in clinical trials, second allo-SCT should be considered for patients with late (≥12 months) relapses after the first allo-SCT. If possible, haploidentical donors should be selected for second allo-SCT and patients should be in complete remission before the transplant.